Persistent bradycardia after hypoglycaemia: a case report and a brief literature review - Beatrice Gasperini; Pierpaolo Lamanna; Rocco Serra; Roberto Montanari; Antonio Cherubini; Emma Espinosa (Geriatric Care, 2019)
Hypoglycaemia can cause cardiac arrhythmias such as QT interval prolongation and ventricular arrhythmias. Supraventricular arrhythmias and sinus bradycardia were rarely reported. We present the clinical case of an 84- year-old man who developed a persistent bradycardia after a hypoglycaemic episode. After restoration of normoglycaemia, bradycardia persisted for almost eighteen hours, without QT prolongation or any symptoms. Hypoglycaemia is an unusual cause of bradyarrhytmias mainly mediated by neurologic and endocrine systems. Our clinical case supports recent recommendations for more relaxed inpatient glycaemic targets in frail older adults who may be particularly vulnerable to hypoglycaemia and its consequences.